Anti-bullying campaign at the Mambaus Sholihin Islamic Boarding School 2 Blitar - Iradhad Taqwa Sihidi; Zen Amirudin (Community Empowerment, 2022)
Bullying has evolved into a very dangerous specter in the educational sector. Schools, which should be a place for kids to develop humanist, dialogical, and sympathetic character, have instead become hotbeds of violence. At the Modern Mambaus Sholihin Islamic Boarding School 2 Blitar, this community service strives to promote a comprehensive and critical awareness of bullying through campaigns. This program's implementation strategy is multi-tiered, beginning with observation, seminars, and mentoring (evaluation). The program can help students have a better understanding and awareness of how to prevent bullying in the Santri community. Therefore, understanding the different types of bullying and the hazards it poses to victims' physical and emotional health inspires a desire to establish a social environment free of bullying.